Relatório da reportagem multiplataforma à luz do jornalismo literário: os guardiões da Igreja São Francisco - Andrade, Luis Eduardo Meira de (2020)
The present work reports the construction of the web report entitled “The guardians of São Francisco”, built in the light of Literary Journalism, having as main object the São Francisco Cultural Center, an ecclesial construction dating from the 16th century, which has a direct relationship with the city João Pessoa, capital of Paraíba. This work aims to produce content that brings a different approach to a theme that is usually explored by different communication channels. To this end, it uses literary journalism, multimedia journalism, multiplatform journalism and web journalism resources to promote a unique and complex journalistic experience. It applies the principles of New Journalism which refers to the journalistic production of a literary character focused on everyday facts, especially in the perspective of Talese (1980), namely, the construction of scenes, detailed description and humanization of the characters. At the same time, in which it uses, both in the form and in the content of the foundations of multiplatform journalism and webjournalism Canavilhas (2014), such as multimedia, interactivity and hypertextuality. The report details the procedures selected for the production of the report constructed through the reports of five characters who are related to the place: the director of the Cultural Center, the administrator of one of the chapels, a tour guide, an ex-student and a car keeper.